The Challenge of Folklore to Medieval Studies - John Lindow (Humanities, 2018)
When folklore began to emerge as a valid expression of a people during the early stages of national romanticism, it did so alongside texts and artifacts from the Middle Ages. The fields of folklore and medieval studies were hardly to be distinguished at that time, and it was only as folklore began to develop its own methodology (actually analogous to medieval textual studies) during the nineteenth century that the fields were distinguished. During the 1970s, however, folklore adopted a wholly new paradigm (the “performance turn”), regarding folklore as process rather than static artifact. It is here that folklore offers a challenge for medieval studies, namely to understand better the oral background to all medieval materials and the cultural competence that underlay their uses.